The Adhesive Glands during Embryogenesis in Some Species of Phyllomedusinae (Anura: Hylidae) - Vera Candioti, Florencia; Taboada, Carlos; Jose Salica, Maria; Baldo, Diego; Faivovich, Julian; Baeta, Delio [UNESP] (Soc Study Amphibians Reptiles, 2017)
Among anuran embryonic structures, the adhesive (cement) glands appear posterolaterally to the stomodeum and produce a mucous secretion that adheres embryos to surfaces in and out of the egg. In this paper, we study the ontogeny of the adhesive glands in five species of Phyllomedusa representing the two main clades recognized in the genus, plus embryos of Agalychnis aspera and Phasmahyla cochranae. Clutches were collected in the field, and embryos were periodically fixed to obtain complete developmental series and then studied with a stereomicroscope, scanning electron microscopy and routine histological techniques. Structural variations include glands absent (in P. cochranae and Phyllomedusa boliviana), functional club-shaped glands (morphogenetic Type C in Phyllomedusa sauvagii, Phyllomedusa iheringii, and Phyllomedusa tetraploidea), and an unusual Type C-like pattern in Phyllomedusa azurea, characterized by large, oblong glands in a horseshoe-like disposition around the oral disc. This latter gland configuration is similar to that of A. aspera. Interspecific variations also include the arrangement and regression pattern of the secretory region, which are in turn different from those of Type C glands in other clades. To interpret the origin and evolution of gland developmental patterns in the group, we still need information on gland occurrence and development in the basal genera of Phyllomedusinae (Phrynomedusa and Cruziohyla) and in the basal taxa of the two major clades of Phyllomedusa.